Clinical outcomes of intravitreal treatment for ocular toxoplasmosis: systematic review and meta-analysis - Lutiana Amaral de Melo; Mayara Rodrigues Brandão de Paiva; Gabriella Maria Fernandes-Cunha; Armando Silva-Cunha; Marcos Paulo Gomes Mol; Sílvia Ligorio Fialho (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: Ocular toxoplasmosis is the leading cause of infectious posterior uveitis worldwide, accounting for 30-50% of all cases in immunocompetent patients. Conventional treatment is associated with adverse effects and does not prevent recurrence. Intravitreal drug administration can improve disease outcomes and reduce side effects. Herein, we conducted a systematic review and meta-analysis on the efficacy of intravitreal injections for treating ocular toxoplasmosis. Methods: The systematic search was conducted using PubMed, SciELO, and Google Scholar with the descriptors “ocular toxoplasmosis” AND “intravitreal”. We analyzed studies that met the inclusion criteria, i.e., experimental cases in patients treated intravitreally for ocular toxoplasmosis. Considering the systematic review, we focused on the number of intravitreal injections, the therapeutic drug class, and the presence of preexisting conditions. To assess the efficacy of intravitreal injections, a meta-analysis was performed using visual acuity, side effects, disease recurrence, and inflammatory responses as variables. Results: Intravitreal injection-induced side effects were rarely observed (0.49% [0.00, 1.51%] ). The use of antiparasitic and anti-inflammatory drugs afforded improved visual acuity (99.81% [98.60, 100.00%]) and marked effectiveness in treating ocular toxoplasmosis. Conclusions: Intravitreal injections may facilitate the successful treatment of ocular toxoplasmosis. However, clinicians should carefully evaluate the presence of preexisting conditions for ocular toxoplasmosis or previous diseases, as these can impact the decision to administer intravitreal injections.